Metaphysical Hermeneutics - Díaz Perojo, Roberto Luis (Analysis. Journal of Philosophical Research, 2025)
Metaphysical Hermeneutics presents a conceptual singularity that simultaneously integrates a type of knowledge, a vital relation of the subject and a methodologically rigorous formal systematisation. This singularity lies in a novel and complex staging of metaphysics, far removed from the traditional negative judgements, and presented instead, in the form of a vindication of its philosophical role, as a generic structure of hermeneutic procedures. In this key, Jean Grondin succeeds in testifying from a plural approach: the communicating vessels between being, the meaning of things and understanding, as constitutive cores of philosophical work. This proposal, however, poses significant challenges in a contemporary world where hermeneutics has turned towards the critique of grand narratives and the revision of ontological frameworks from situated, decolonial or technodiscursive perspectives.